Pre-feasibility study for the production of 2,5-DMF as a renewable and clean energy bicomponent to enhance octane biofuels Talara - PETROPERÚ SA - Lozano Flores, Gian Percy (2012)
It is very important scientific interest in developing new technologies for the conversion of renewable resources in sustainable energy, chemicals and biomaterials, as it involves environmental, political, and economic issues related to dependence that society has for the use of petroleum feedstock. The oil has other uses as raw material for about 95% of the carbon-containing chemicals used in our society. Under this, the interest in the study of furan components is to check viability of production, preparation and application thereof. One (enzymatic and chemical) hybrid-chemical route sucro area for the production of 2,5-dimetilfurano (DMF) as bicomponent clean renewable energy is presented in this research to improve the octane biofuel Talara Refinery - PETROPERÚ SA using biomass as feedstock. Compared to ethanol, 2,5-dimethylfuran (DMF) has a higher energy density (more than 40%), a boiling point higher (20 ° C above), and is not soluble in water. The developed technology creates a new route to transform native abundant renewable biomass resources in a convenient liquid biofuels for the transport sector, and may reduce the need for oil and fossil fuels. It also estimates the conversion of different lignocellulosic wastes in DMF, highlighting the bagasse as main attraction for the production of 0,119 L of DMF / kg of dry bagasse, with the Department of Piura a key development area.